Frontiers in lung cancer. - Moghissi, K. (Keyvan); Kastelik, Jack; Barber, Philip; Sardari Nia, Peyman (Frontiers in Lung Cancer Ser., 2020)
Perspectives in Lung Cancer compiles basic and advanced topics on lung cancer pathology and treatment in a single volume. Chapters introduce the reader to chest and lung anatomy followed by the biology of lung cancer. Subsequent chapters delve into diagnostic methods for lung cancer while progressing into treatment options. The book culminates into an explanation of the concept of the Lung Cancer Centre, which is a representation of the editors' vision for organizing a lung cancer treatment unit. Key features: Organises key topics covering both standard and avante-garde topics related to lung.